AN ANALYTICAL STUDY OF CHANGES IN THE LEARNING PARADIGM FROM INSTRUCTIONAL INTERACTIONS TO PEDAGOGICAL INTERACTIONS - Adawiyah Pettalongi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
Interactions between students and teachers are a role in the learning process. Learning interaction is both a social contact activity and a teaching and learning process. In addition to instructional interactions, learning interactions can also occur in the form of pedagogical interactions. Using a qualitative approach, this study is library-based research. Various literature on educational theory were reviewed for material. Using content analysis and comparison techniques, the data were then studied to identify fundamental developments in educational thought. According to the findings of this study, successful learning consistently pursues and executes the process of transferring both information and value. In addition to procedural and intellectual partnerships, the learning process includes emotional relationships that encompass affection, mutual regard, and respect. Additionally, learning must be founded on an equitable connection between teachers and students within the context of educational values. The engagement of mental dimensions enables a learning process that is not just intellectually oriented, but also emotionally and spiritually oriented.